Pertanggungjawaban Pidana Influencer atas Endorse Judi Online: Kajian Kejahatan Siber di Indonesia - Muhammad Ramadhan Ridwansyah; Fatihatun Naja; Siti Aisah; David Nugraha Saputra (Jurnal Hukum Lex Generalis, 2025)
The rise of social media has established influencers as powerful agents in digital promotion. However, their involvement in promoting online gambling presents complex legal challenges. This study employs a normative juridical approach to analyze the criminal liability of influencers based on the Indonesian Criminal Code (KUHP) and the Electronic Information and Transactions Law (UU ITE). Findings reveal that although regulations prohibit online gambling, law enforcement faces significant challenges, particularly in proving intent. Strengthening regulations, enhancing digital literacy, and fostering cross-sector collaboration are essential to prevent illegal content dissemination and reinforce legal certainty in the digital realm.